DAMPAK PENERAPAN PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) TERHADAP KEBIJAKAN AKADEMIK DI PERGURUAN TINGGI - Hassanah, Hetty; Tua Situmeang, Sahat Maruli; Pane, Musa Darwin; Wahyudi, Wahyudi; Sari, Febilita Wulan (Komunitas Manajemen Kompetitif, 2024)
This study aims to find the impact of the implementation of the Independent Campus, Freedom to Learn programme on academic policies in higher education, especifically the Faculty of Law, Indonesian Computer University so that this programme can be implemented more optimally in the future. The study conducted by the author is descriptive analytical with a normative juridical approach. The resulting data is analyzed in a qualitative juridical manner so that the hierarchy of laws and regulations can be considered and can guarantee legal certainty. Based on the results of the study, it can be seen that the Independent Campus, Freedom to Learn programme organized by the Unikom Faculty of Law has met the expectations of both the institution and its partners, although there are still shortcomings in its implementation practice, including internal policy alignment. The increasing competence of students participating in the Independent Campus, Freedom to Learn programme is a factor that needs to be followed up by the program, as well as the need to expand collaboration with various parties/partners to provide wider opportunities for students. The Independent Campus, Freedom to Learn programme at the Faculty of Law, Unikom, still has obstacles, namely related to the addition of new partners, curriculum adjustments and adjustments to the Academic Information System that accommodates the Independent Campus, Freedom to Learn programme. This research is a media for searching for problems, analyzes and solutions needed in the implementation of the Independent Campus, Freedom to Learn programme at the UNIKOM Faculty of Law, so that appropriate solutions can be found for these problems, especially related to internal policies within the UNIKOM Faculty of Law relating to with the implementation of the Independent Campus, Freedom to Learn programme.